2019
DOI: 10.3390/su11092521
|View full text |Cite
|
Sign up to set email alerts
|

Comfort First! Vehicle-Sharing Systems in Urban Residential Areas: The Importance for Everyday Mobility and Reduction of Car Use among Pilot Users

Abstract: The aim of this study is to explore to what extent a vehicle-sharing system (VSS) that includes electric bicycles and cars, connected to a block of apartments in a middle-sized city in Sweden, can cater for individuals’ everyday mobility needs and reduce the need to own a car. The study connects to two different research areas: the usage of VSS and mobility transitions through pilot projects. Our results show a reluctance to voluntarily sacrifice comfort regarding everyday energy use. Owning and using a privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Compared to door-to-door car trips, travelers usually face extra physical, cognitive and affective efforts if they would take an inter-modal trip (Stradling et al, 2000): physical effort is needed during transfer between modes when the stations for different modes are not at the same location; it is also cognitively demanding to deal with searching and payment of different mobility services; as a result, these extra efforts will harm the perception of shared mobility services as an inconvenient and uncomfortable option compared to car (Berg et al, 2019). Therefore, the integration shall aim to reduce these different aspects of extra effort and lower the barriers for switching toward adopting shared emobility service.…”
Section: Relations Between Different Modes: Complementarymentioning
confidence: 99%
“…Compared to door-to-door car trips, travelers usually face extra physical, cognitive and affective efforts if they would take an inter-modal trip (Stradling et al, 2000): physical effort is needed during transfer between modes when the stations for different modes are not at the same location; it is also cognitively demanding to deal with searching and payment of different mobility services; as a result, these extra efforts will harm the perception of shared mobility services as an inconvenient and uncomfortable option compared to car (Berg et al, 2019). Therefore, the integration shall aim to reduce these different aspects of extra effort and lower the barriers for switching toward adopting shared emobility service.…”
Section: Relations Between Different Modes: Complementarymentioning
confidence: 99%
“…This is in line with previous research (Sjöman, Ringenson & Kramers, 2020) which showed that most participants were insensitive to the costs associated with the use car. Instead, convenience, in the sense of how easy, effortless, and smooth the service is, seems to be more important (Berg, Henriksson & Ihlström, 2019). Another, or complementary, explanation for the modal change effect in all three groups is that individuals who agreed to participate in the study might have reached further in their transition to change than those not willing to participate (Wallén Warner, Björklund & Andersson, 2021).The three groups might even have different reasons for increasing their use of public transport overall and decreasing their use of the car.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been carried out to investigate the determinants of present modal choice, and their significant effects (Acker et al, 2007;Berg, Henriksson & Ihlström, 2019;Cao, 2015;Cervero & Day, 2008;Cheng, Chen, De Vos, Lai, & Witlox, 2019;Naess, 2006;Naess, 2013). Those studies contributed to a comprehensive knowledge foundation for understanding the dependencies of travel behavior from different perspectives among which, individual and environmental aspects formed the key factors.…”
Section: Modal Choicementioning
confidence: 99%
“…The pattern of space utilization that tends to change in the corridor of the Urip Sumoharjo Perintis Kemerdekaan road is positively associated with an increase in population mobility and an increase in the flow of transportation movements from the direction of Maros Regency to the city center, industrial areas, ports, trade centers, and Hasanuddin International Airport. Thus, it is very important to control building densification and reduce private vehicle ownership towards the use of public transport [106]. Furthermore, it is very important for the development of freight transport to be aligned with efforts to save the environment in a sustainable manner [107].…”
Section: Environmental Management Strategy and Air Pollution Controlmentioning
confidence: 99%